Direction-finding methods for cyclostationary signals in the presence of coherent sources. - Yung-Ting Lee (IEEE Transactions on antennas and propagation)
By exploiting the signal cyclostationarity, conjugate cyclic MUSIC presented by Gardner (1994), has been shown to be effective in performing signal-selective direction finding. However, a direct application of conjugate cyclic MUSIC in the presence of coherent signals of interest (SOIs) will result in ambiguity. To tackle the drawback of conjugate cyclic MUSIC, we present a scheme called the Hankel approximation method (HAM) in conjunction with conjugate cyclic MUSIC to cope with the performance deterioration due to coherent SOIs for a uniform linear array. Theoretical analysis shows that at least 2K sensor elements are required to resolve K coherent SOIs. Making use of the forward/backward (F/B) technique presented by Pillai and Kwon (1989), F/B HAM is further developed, which requires [3K/2] sensor elements to decorrelate K coherent SOIs, where [x] represents the integer part of x. Several simulation examples are also presented for illustrating the effectiveness of the proposed methods